2017
DOI: 10.3329/bjmb.v8i2.33279
|View full text |Cite
|
Sign up to set email alerts
|

Status of Serum Copper and Zinc in Pre-Eclampsia

Abstract: Pre-eclampsia is a multisystem and multifactorial disease that affects both mother and fetus by endothelial dysfunction and intrauterine growth retardation. It is thought that pre-eclampsia is associated with an imbalance of increased lipid peroxides and decreased antioxidants. Dietary deficiency or excess of copper, zinc or other micronutrients play important role in the pathogenesis of pre-eclampsia because nutrients can modulate oxidative stress by increasing or decreasing free radicals or antioxidants and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…In the present work, both groups were comparable as regard to patient age and gestational age. These results are comparable to those reported by Muna et al [33] and others [35][36] .…”
Section: Farzin and Sajadisupporting
confidence: 93%
See 1 more Smart Citation
“…In the present work, both groups were comparable as regard to patient age and gestational age. These results are comparable to those reported by Muna et al [33] and others [35][36] .…”
Section: Farzin and Sajadisupporting
confidence: 93%
“…Zinc deficiency in PE may result from hemodilution caused by fluid retention, endogenous steroid production and fetal uptake of zinc from her mother circulation. It may also be due to reduced levels of zinc binding protein [33] .…”
Section: Farzin and Sajadimentioning
confidence: 99%
“…Significantly higher serum copper was observed in the preeclamptic women in this study. Contradictory to the above study low level of serum copper was mentioned by Gayathri B and Lewandowska M et al [21,22] and no significant change in serum copper and serum zinc were reported by FZ Muna et al in preeclampsia [23]. In preeclampsia, it is presumed that mobilization of copper from maternal tissue, especially from damaged liver occurs due to vasoconstriction which may be responsible for raised serum copper.…”
Section: Discussionmentioning
confidence: 85%